2010
DOI: 10.1128/mcb.01511-09
|View full text |Cite
|
Sign up to set email alerts
|

PRH/Hhex Controls Cell Survival through Coordinate Transcriptional Regulation of Vascular Endothelial Growth Factor Signaling

Abstract: The proline-rich homeodomain protein (PRH) plays multiple roles in the control of gene expression during embryonic development and in the adult. Vascular endothelial growth factor (VEGF) is a mitogen that stimulates cell proliferation and survival via cell surface receptors including VEGFR-1 and VEGFR-2. VEGF signaling is of critical importance in angiogenesis and hematopoiesis and is elevated in many tumors. Here we show that PRH binds directly to the promoter regions of the Vegf, Vegfr-1, and Vegfr-2 genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(75 citation statements)
references
References 78 publications
5
70
0
Order By: Relevance
“…Having established that there is indeed a direct link, we next asked whether HHEX/PRH was important for the growth of human T-ALL cells. Using vectors previously established to produce effective knockdown of HHEX/PRH (Noy et al, 2010) we now show that following expression of short hairpin RNA against HHEX/PRH in the LMO2-expressing nontranslocated cell line Molt4, cells were unable to grow, whereas cells transfected with a control vector could expand as expected (Figure 7g). Taken together, these results not only support the existence of a highly connected LMO2, FLI1, ERG triad in T-ALL but also demonstrate that HHEX is a direct target of this triad with a likely role in human T-ALL (Figure 7h).…”
Section: Lmo2/erg/fli1 Function Upstream Of Hhex/prh That Is Requiredmentioning
confidence: 89%
See 1 more Smart Citation
“…Having established that there is indeed a direct link, we next asked whether HHEX/PRH was important for the growth of human T-ALL cells. Using vectors previously established to produce effective knockdown of HHEX/PRH (Noy et al, 2010) we now show that following expression of short hairpin RNA against HHEX/PRH in the LMO2-expressing nontranslocated cell line Molt4, cells were unable to grow, whereas cells transfected with a control vector could expand as expected (Figure 7g). Taken together, these results not only support the existence of a highly connected LMO2, FLI1, ERG triad in T-ALL but also demonstrate that HHEX is a direct target of this triad with a likely role in human T-ALL (Figure 7h).…”
Section: Lmo2/erg/fli1 Function Upstream Of Hhex/prh That Is Requiredmentioning
confidence: 89%
“…A total of 5 Â 10 6 Molt4 cells were electroporated using 10 mg green fluorescent protein short hairpin RNA (control) or 5 mg PRH49 and 5 mg PRH51 short hairpin RNA plasmids in combination previously as described (Noy et al, 2010). Cells were selected with 1 mg/ml puromycin and viable cells were counted daily for 14 days.…”
Section: Knockdown Of Hhex/prhmentioning
confidence: 99%
“…PRH can control cell proliferation via the posttranscriptional regulation of cyclin D mRNA transport (2). In addition, our previous work has shown that in leukaemic cells, PRH directly represses multiple genes that encode proteins involved in VEGF signalling including Vegfa and Vegfr-1 (31). In these cells VEGF acts as an autocrine growth factor and the transcriptional regulation of these VEGF signalling genes by PRH controls cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…In these cells VEGF acts as an autocrine growth factor and the transcriptional regulation of these VEGF signalling genes by PRH controls cell survival. The extent to which these modes of cell survival control operate in other cell types is not known, although in breast cancer MCF-7 cells, PRH regulates the transcription of Vegf receptor genes and a PRH knockdown increases cell growth (31). In endothelial cells PRH over-expression also controls VEGF signalling genes and alters cell migration and invasion (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation